Building a Sustainable Future: Investigating the Role and Contributions of Higher Education Institutions Instructors in Promoting Social Sustainability-Empirical Evidence from Ethiopia - Mestawot Beyene Tafese; Erika Kopp; Habte Tadesse Likassa (MDPI AG, 2024)
The need for social sustainability through education is greater than ever. Despite numerous studies on this topic, there is still a gap in the research on the role and contribution of public higher education instructors in social sustainability. To address this, the researchers of this study conducted a study on the contributions of instructors in public higher education to social sustainability in Ethiopia. The study aimed to provide evidence for policy briefs and guide public universities. A quantitative method was employed, and the reliability of the structured questionnaire was tested using Cronbach's alpha. The data were analyzed by descriptive and inferential statistics. The findings revealed that 62.9% of instructors contributed to social sustainability, with significant predictors identified at 5%. Research and applied university instructors were 3.36 and 2.20 times more likely, respectively, to contribute compared to comprehensive universities. Furthermore, the results indicated that females were 0.64 times less likely to participate compared to males. Instructors who were optimistic about research implementation were 4.9 times more likely to engage, and those indicating "probably yes" were 18.5 times more likely as compared to the reference category. Educators involved in multiple roles were 0.13 times less likely to contribute than those focused solely on teaching. Ethiopia's Ministry of Education and university leaders should support female teachers and master's-level faculty at applied and comprehensive universities.